Agregar al libro iii del código orgánico de la niñez y adolescencia la oficina técnica de protección de los derechos de la niñez y adolescencia de acuerdo a las facultades que el código orgánico de organización territorial, autonomía y descentralización (COOTAD), otorga a los gobiernos autónomos descentralizados - Albán Ortega, Edwin Fabián (2016)
Present thesis called “ADD TOBOOK III OF THE ORGANIC CADE OF CHILDRENAND ADOLESCENTS THE TECHNICAL OFFICE FOR THE PROTECTION OF THE RIGHTS OF CHILDREN ON ADOLESCENTS OCBARDNY TO THE NOWERS BESTOWED BY THECOOTAD TO THE AUTONO NOUS MOUS JOVERNNCATS”, is a problem that addresses a complete legal and social importance, which affects society as a whole family especially where they live in total abandonment, being checked out so there is no organism to ensure proper implementation an defense of their rights. As is known by all citizens, the rights of children and adolescents are considered essential to the development agencies of nations, in our case Ecuadorian law protects these rights, the constitution of the Republic of Ecuador, treaties International an the Code of Childhood and Adolescence, so lawyers specializing in juvenile matters, provide that persons subject to rights are the ability to demand and take responsibility for their rights and obligations, so that the State has the duty leading ensure effective enforcement of their rights, and in doing so comply with the provisions regarding the doctrine of integral protection. The Code of Children and Adolescents, provides for the National Council for childhood and Adolescence as a collegial organism, composed of representatives of state and civil society whose function are intended to define and assess compliance with the national policy of protection comprehensive childhood and adolescence, as well as promote the creation and the technical office for the protection of the rights of children on adolescents so my study is aimed to show that no default under full protection, as our stable legislation and currently are many gaps and a total lack of children and adolescents in the rural parishes of our country, the cootad to the autono nous mows jovernncats, hence the need for parish councils defending the rights of children and adolescents. Another issue addressed by this thesis research, is related to the organization of parish councils, duties, obligations and responsibilities, this in accordance with the provisions of the Law to eliminate the violation of the rights of children and adolescents in the rural parishes of our country.